Parametric and subsurface analysis of MWCNT alumina composites in WEDM process. Issue 2 (1st February 2018) - Annebushan Singh, Meinam; Kumar Sarma, Deba
Abstract: Machining of ceramics in electrical discharge process is a big challenge till date owing to its low electrical conductivity. Reinforcing with a conductive filler increases the electrical conductivity thereby allowing the ceramic composite to be successfully machined. Multi walled carbon nanotubes have the capability of increasing the electrical conductivity of ceramic composites to a great extent with a low concentration. The present work analyses the effect of input parameters towards machining of multi walled carbon nanotubes filled alumina composites in wire electrical discharge machining process. The material removal rate and the surface characteristics are found to be affected non-linearly by various input conditions. A mixed melting-evaporation and spalling effect are found as the material removal mechanism. The melting-evaporation is observed to be more dominating at lower current while spalling at higher current. The subsurface analysis indicates the presence of porous recast layer and micro cracks in the machined workpiece.